Maiden Castle, Dorset - Wheeler, R. E. M. (Reports of the Research Committee of the Society of Antiquaries of London, 1943)
This is an account of the archaeological excavations of Maiden Castle, in Dorset, England. Included are descriptions of artefacts such as pottery and human remains, together with an account of the methodology used to unearth these.